Microbial community occupying cocoa branch and petiole with vascular streak dieback disease symptoms. Issue 2 (July 2021) - Junaid, M; Haerunnisa, M; Amin, N
Abstract: Vascular Streak Dieback (VSD) disease caused by Ceratobasidium theobromae is the most severe emerging cocoa disease in Southeast Asia. Once the tree is infected, tree defoliation will occur as leaf senescence followed by leaf falls. VSD to have associated with endophytes. However, a fundamental question is whether a similar microbe inhabiting vascular tissue of branch and petiole is entire or patchy? The aim of research was to track and quantify microbial diversity associated with VSD symptoms occupying branches and petiole throughout the stem in different clones. The study focused on VSD symptoms expressing in local (Sulawesi 02), susceptible (RCC 70), and resistant (MCC 02) clones to VSD disease. Sample collection was conducted in Lili Riaja, Soppeng District. The 30 cm-branch with the attached petiole of interest was cut into small pieces 1 cm and transferred into water agar medium before submersion into 2.5% NaOCl for 3 minutes, 70% alcohol for 2 minutes and sterilized water for 1 minute. Morphological characterization followed by microscope check was determined to microbial genera. Eight different fungal communities occupying branch and/or petiole consisted of Cladosporium sp., Fusarium sp., Colletotrichum sp., Penicillium sp., Aspergillus sp., Moniliophthora sp., Lasiodiplodia sp., Curvularia sp. and one Oomycete Phytophthora palmivora . Among occupants in branch and petiole, Fusarium sp. and Colletotrichum sp. were the most frequent. Only one Oomycete Phytophthora palmivora occupying clone samples was found. The most diverse microbes were found to associate with Sulawesi 02 and RCC 70 clones, while fewer microbes were detected with MCC 02 clone.